The Use Of Students’ Team- Achievement-Division Technique To Improve Students’ Reading Skill - Tri Wahyuni; Iskandar Abdul Samad; Diana Achmad (Universitas Syiah Kuala, 2019)
This quantitative study was aimed to find out whether the use of Students -Team-Achievement- Division (STAD) technique can improve the students’ reading skill in understanding narrative text among the first grade students at SMK Harapan Pangkalan Berandan. The researcher used simple random sampling to choose the sample.This research utilized three phases (pre- test, treatment and post-test) to collect the data. X AK -1 (Accountancy Class) of SMK Harapan Pangkalan Berandan was chosen as the sample in this study. This research focused on five aspects of reading comprehension mainly in identifying main idea, finding detail information, making reference, vocabulary and inference. The data was analyzed by using t-test. The analysis of t-test shows that t-value t-table or 5,16 2,04 at the level of significance 0,05 with the degree of freedom (df) 29. It means that the alternative of hypotheses (Ha)was accepted and (HO) was rejected. Furthermore, the result of this study shows that the mean score of pre- test was 44,6 and the mean score of post-test was 78,3. While the gain score was 33,7. Based on the findings the students’ reading skill in narrative text are improved after being taught by using STAD technique.